Impact of Water Safety Plans on Health and Water Quality: Scoping Review - Lalu, Nur Ayini S (BKM Public Health and Community Medicine, 2024)
Purpose: The implementation of Water Safety Plans (WSPs) has become a major focus of efforts to improve water quality and its impact on human health in various countries. This scoping review aims to summarize research results related to the implementation of WSPs in reducing the risk of water contamination and its impact on health. Methods: A scoping review was conducted by reviewing several international journals that examined the application of WSPs from 2010 to 2023. Data extracted included publication characteristics, the impact of WSPs on water quality, the impact of WSPs on health, and the number of systems intervened or analyzed. Results: The scoping review showed that the implementation of WSPs has had a positive impact on water quality with significant reductions in microbiological parameters such as E. coli, improved water treatment effectiveness, and reduced risk of contamination by microbial pathogens. Health impacts were also seen through reduced incidence of water-related diseases such as diarrhea and gastroenteritis. Conclusion: The consistent implementation of Water Safety Plans (WSPs) contributes positively to water quality and human health through controlling the risk of microbiological and chemical contamination. However, it is important to pay attention to the completeness and quality of WSPs implementation to maximize their benefits in maintaining safe drinking water for the community.